Hubungan Keeper dan Harimau Sumatera di Taman Marga Satwa Budaya Kinantan, Bukittinggi, Sumatera Barat - Basyarul Aziz; Khoirun Nisa Aulia Sukmani (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This paper discusses multispecies anthropology, which refers to an approach involving various forms of life, recognizing that humans are not the only significant subjects in ecosystems. It is an anthropological approach that expands the focus of study to include the relationships between humans and other species, including animals, plants, microorganisms, and non-human entities. The paper explores the relationship between humans and Sumatran tigers at the Kinantan Wildlife and Cultural Park in Bukittinggi.The Sumatran tiger is critically endangered due to habitat loss, ecosystem degradation, and most importantly, the high-intensity human-tiger conflict. This has created conditions where tigers are relocated to enclosures or zoos. Tigers in zoos are often explored for economic or research purposes, creating a new agency for tigers as both "objects and subjects" in the narrative of conservation. Additionally, it creates a complex and mutually influencing relationship between humans and tigers.To preserve the Sumatran tiger as a "wild" species in zoos, certain practices resembling domestication have been implemented by keepers, leading to new ways of interacting with and perceiving this species. Using a qualitative descriptive method and a performative approach through the animal focal sampling method to observe the daily behavior of Sumatran tigers, this study illustrates how different "tigers" are "created" through interaction practices and how a performance of wildlife coexists with domestication practices within the tiger enclosure.The paper examines specific breeding practices and how feeding, breeding, and captivity entangle human and animal lives.The researcher has also explored various ways of care enacted by keepers, ranging from close, embodied interactions. By focusing on the interrelated practices within the zoo, the paper aims to use empirical descriptions to argue about the relationships within the processes of becoming and the formation of a world—a world that is not static but made through the practices of both human and non-human agents.